SINTESIS ESTER GALAKTOSA ASAM LEMAK DARI METIL ESTER MINYAK BIJI KOPI ARABIKA (Coffea arabica) DAN GALAKTOSA ASETAT - Josua K. Panannangan; Daniel Daniel; Chairul Saleh (PROSIDING SEMINAR KIMIA, 2017)
The synthesis of ester galactose fatty acid from methyl ester of arabica coffee seed oil (Coffea arabica) and galactose acetate with a toxic solvent-free synthesis process has been performed. Methyl ester oil of coffee beans is synthesized from coffee seed oil that has been macerated for 3 days with oil content of 17% and the result of methyl ester synthesis of coffee seed oil has a yield percentage of 87.93% with methanol reaction medium with 1% H2SO4 catalyst. Galactose acetate was synthesized from galactose and anhydrous acetic acid on a 1: 1 ratio resulting in galactose acetate with a yield percentage of 91.29%. The synthesis of fatty acid galactose ester from methyl ester coffee seed oil and galactose acetate was synthesized with a 1: 1 mole ratio using a 1 M M NaHCO3 catalyst with a temperature of 80-100 ºC for 6 hours yielding galactosil ester of fatty acid coffee seed oil. FTIR analysis showed that ester group formed from coffee seed oil methyl ester at wave number 1745,58 cm-1. FTIR analysis of galactosil acetate showed the presence of ester group formed from galactose at wave number 1728,22 cm-1. FTIR analysis of galactose oil seed oil ester showed the presence of ester group at wave number 1743,65 cm-1 and group (CH2)n at wave number 721,38 cm-1 with value of HLB obtained 3,494. Keywords: Coffee bean oil, galactose acetate, interesterification, fatty acid ester galactose